2023
DOI: 10.1021/acs.analchem.3c02540
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Application of Artificial Intelligence-Based Spectral Data Interpretation: A Perspective

Xi Xue,
Hanyu Sun,
Minjian Yang
et al.

Abstract: The interpretation of spectral data, including mass, nuclear magnetic resonance, infrared, and ultraviolet–visible spectra, is critical for obtaining molecular structural information. The development of advanced sensing technology has multiplied the amount of available spectral data. Chemical experts must use basic principles corresponding to the spectral information generated by molecular fragments and functional groups. This is a time-consuming process that requires a solid professional knowledge base. In re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…Moreover, the advancement in soft computing has revolutionized data analytics for sensor development. The rapid emergence of deep learning has been successfully applied to improve the analytical performance of colorimetric determination (e.g., UV-Vis spectrophotometer and colorimetric test paper), including denoising, recognition, and summary of every small characteristic change from each image [49][50][51][52]. One example is Deep Convolutional Neural Networks (DCNNs) [51].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, the advancement in soft computing has revolutionized data analytics for sensor development. The rapid emergence of deep learning has been successfully applied to improve the analytical performance of colorimetric determination (e.g., UV-Vis spectrophotometer and colorimetric test paper), including denoising, recognition, and summary of every small characteristic change from each image [49][50][51][52]. One example is Deep Convolutional Neural Networks (DCNNs) [51].…”
Section: Plos Onementioning
confidence: 99%
“…Structures are identified by comparing the query spectra with each spectrum in the reference library. , The large chemical shift ranges and narrow peak widths contribute to the prevalence of 13 C spectral-library-matching systems in compound identification . However, as the traditional libraries contain only tens or hundreds of millions of known compound structures, they do not meet the growing demand for structure identification. ,, Over the last few decades, with the significant advancement in artificial intelligence, deep learning has been developed in the field of analytical chemistry …”
Section: Introductionmentioning
confidence: 99%
“…The study showed that under single algorithm conditions, the accuracy of brand classification for dairy products exceeded 90%, and when these algorithms were combined and coordinated, the accuracy could reach 99% ( Zikang et al, 2024 ). However, there are also some issues that urgently need improvement, such as spectral feature analysis ( Ji et al, 2023 ; Xue et al, 2023 ). For machine learning discriminative algorithms, they often act as a black box with limited interpretability.…”
Section: Introductionmentioning
confidence: 99%